(untitled) (Simbiótica. Revista Eletrônica, 2024)
This text aims to investigate the unheimlich, feeling present in Freud’s 1919 text, using the interpretation made by Lacan to develop his object a to defend the aspect present in this investigation in a possible method for psychoanalysis in the face of suffering, anguish and malaise in situations of indetermination. Within conceiving the unheimlich under Lacanian lenses, there is a clinical method that allows a dialectical movement in psychoanalysis to deal with the creation of a necessary grammar for an experience of subjective suffering.